Reforming the pre-legislative process - Khaitan, T (2011)
Reforms are required to ensure that public debate and deliberation precede rather than merely follow legislative enactments. They may strengthen the State's capacity to draw upon the expertise and experiences of Indian citizens, and may, ultimately, help us take a few more steps towards evolving into a robust deliberative democracy.